Encyclopedia of consumer culture - Southerton, Dale (Sage, 2011)
"Covers consuming societies around the world, from the Age of Enlightenment to the present, and shows how consumption has become intrinsic to the world's social, economic, political, and cultural landscapes."-Provided by OhioLINK library catalog.